2013
DOI: 10.1016/j.juro.2013.03.112
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Phosphodiesterase Type 5 in the Spinal Cord and its Involvement in Bladder Outflow Obstruction Related Bladder Overactivity

Abstract: Phosphodiesterase type 5 is expressed in the rat spinal cord. Intravenous sildenafil may exert part of its urodynamic effect in rats with partial urethral obstruction/bladder overactivity via an effect on the sacral spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Several previous studies have reported that PDE5‐Is and NO reduce mechanosensitive afferent activity of both A δ‐ and C‐fibres evoked by bladder distension in the rat . However, it is worth noting that these reports of inhibitory effects of PDE5‐Is on bladder afferent discharge were found at higher bladder pressures (30 cmH 2 O) than the voiding threshold in normal rats (about 10–15 cmH 2 O ) possibly reflecting inhibitory effects in a noxious range (i.e., on nociceptors), rather than in the normal range of storage and threshold pressures. This increase in the afferent activity may account for the reduction in the threshold pressure for voiding produced by sildenafil.…”
Section: Discussionmentioning
confidence: 86%
“…Several previous studies have reported that PDE5‐Is and NO reduce mechanosensitive afferent activity of both A δ‐ and C‐fibres evoked by bladder distension in the rat . However, it is worth noting that these reports of inhibitory effects of PDE5‐Is on bladder afferent discharge were found at higher bladder pressures (30 cmH 2 O) than the voiding threshold in normal rats (about 10–15 cmH 2 O ) possibly reflecting inhibitory effects in a noxious range (i.e., on nociceptors), rather than in the normal range of storage and threshold pressures. This increase in the afferent activity may account for the reduction in the threshold pressure for voiding produced by sildenafil.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, this enzyme may have significant effect on the pathogenesis of BPH-LUTS. In addition, there is information stating that PDE5 expression in the spinal cord area is responsible for urination control [14]. Tadalafil administration appeared to increase the amount of cyclic nucleotides in the urinary bladder, prostate and cavernous bodies of penis.…”
Section: Methodsmentioning
confidence: 99%
“…PDE5 is present in the tissue and vasculature of the bladder neck, prostatic urethra, prostate, and corpus cavernosum14,15 and is implicated in the pathology of LUTS/ED 10,16. Furthermore, PDE5 was found to be expressed in the sacral spinal regions and micturition control areas 17. In an animal model of bladder hyperactivity secondary to bladder outlet obstruction, the administration of sildenafil helped alleviate bladder overactivity when administered intravenously and intrathecally, indicating possible neurologic involvement of this class of medications 17.…”
Section: Tadalafilmentioning
confidence: 99%
“…Furthermore, PDE5 was found to be expressed in the sacral spinal regions and micturition control areas 17. In an animal model of bladder hyperactivity secondary to bladder outlet obstruction, the administration of sildenafil helped alleviate bladder overactivity when administered intravenously and intrathecally, indicating possible neurologic involvement of this class of medications 17. In transurethral resection of the prostate specimens, cGMP and cAMP (cyclic adenosine monophosphate) were significantly higher in patients receiving tadalafil or udenafil than in the control group 18.…”
Section: Tadalafilmentioning
confidence: 99%